Health and Social Problems in Indonesian Elderly. How Can Health Care System To Overcome ? - Iwan Rusdi (Caring: Indonesian Journal of Nursing Science, 2019)
Increasing elderly population is a problem in Indonesia. Many problems faced in elderly. Elderly are high risk to experience a disease or illness. As well as, long term care is needed for release the disease. A changing in biopsychosocial also important for service provider to control the effect. Collaboration and partnerships is useful to develop strengthening in creating health care system. Furthermore, policy maker and service provider are also better able to review and refine their existing measure, policies, product and geriatric service, which target elderly population in Indonesia.